Pre-and postoperative factors associated with functional outcomes in patients with posterior malleolar fractures. Issue 6 (June 2022) - Yamamoto, Norio; Iwamoto, Kohei; Tomita, Yosuke; Iwamoto, Yuki; Kiyono, Masahiro; Yoshimura, Masahide; Noda, Tomoyuki; Kawasaki, Keisuke; Ozaki, Toshifumi
Highlights: Previously, the association between pre-and postoperative whole ankle joint factors with postoperative functional outcome was unclear. Our results indicate that postoperative complications are associated with AOFAS scores at postoperative 12 months. In patients with small posterior malleolar fragments, reduction and fixation is not associated with postoperative functional scores. Abstract: Introduction: Recent studies on posterior malleolar fractures mainly focus on the reduction quality and fixation of the posterior fragment since it contributes to ankle stability and articular congruency. However, the association of pre-and postoperative factors considering the whole ankle joint in postoperative functional outcomes remains unclear. Therefore, this study aimed to examine the association between pre-and postoperative variables for postoperative functional outcomes in patients with posterior malleolar fragments (classified as Haraguchi type I or II) and considered the association between reduction and fixation for small posterior malleolar fragments of less than 25% of the intra-articular surface. Methods: This multicenter retrospective cohort study included 110 adult patients who underwent internal fixation for ankle fractures with posterior malleolar fragments. The primary outcome was the American Orthopaedic Foot and Ankle Society (AOFAS) score 12-months postoperatively. As pre-and postoperative variables, the preoperative demographic data, radiographic findings, operative method, postoperative radiographic findings, and complications were evaluated. In addition, univariable and multivariable logistic regression analyses were conducted to examine the association between pre-and postoperative variables and AOFAS scores. Results: Twenty-four (21.8%) cases had postoperative complications. Univariate analysis showed that age was significantly according to AOFAS score-stratified groups in patients with Haraguchi type II fractures. Multivariable logistic regression analysis using bootstrapping in the Haraguchi type II group showed that postoperative complications were significantly associated with low AOFAS scores, indicating poor functionality. In both fracture types, postoperative complications had the highest odds ratio among the explanatory variables. In patients with small posterior malleolar fragments, fragment reduction, fixation, and ankle stability were not associated with AOFAS scores. Conclusions: Our results suggest that postoperative complications were associated with AOFAS scores at postoperative 12 months in patients with ankle fractures with posterior malleolar fragments. In patients with small posterior malleolar fragments, reduction and fixation were not associated with AOFAS scores. Therefore, clinical decisions for posterior fragment fixation should be made based on the possible risk of complications related to the surgical procedures in addition to the posterior malleolar fragment size.